Metastases and Management Evolution: Literature Review - Tomar, Suryapratap Singh (Eastern Green Neurosurgery, 2026)
Introduction: Brain metastases are the most prevalent kind of brain tumor and a frequent side effect of cancer. Brain metastases occur in between 10% and 25% of cancer patients who pass away. A team of medical professionals uses radiation therapy, surgery, and other treatments to treat brain metastases. To lessen the effects of the brain tumor and preserve quality of life, they could combine surgery with additional therapies. Conventional therapy can only cure a small percentage of brain-metastasized tumors, but they can provide palliation and long-term survival with few side effects. This exercise goes over how brain metastases manifest and emphasizes how the multidisciplinary team may help manage them.